2016
DOI: 10.1179/1743294415y.0000000094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma nitriding on nanostructure of TRD coating

Abstract: In this study, the effect of conventional plasma nitriding on chromised tool steel was investigated. The samples were chromised at 11008C for 12 h using thermoreactive diffusion/deposition (TRD). Subsequent tof TRD, specimens were nitrided at 6008C using a DC plasma set-up. Phase composition and surface morphology of the coatings were investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM) respectively. Corrosion resistance of the samples was investigated by polarisation corrosion test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Nowadays, diffusion coatings on gear materials via carburizing, nitriding, carbonitriding, boronizing, and chromizing to improve the wear resistance of carbon steels has been widely reported [7][8][9][10]. In addition to improvement on the hardness and wear resistance, boronizing and chromizing treatment can also improve the corrosion resistance and high-temperature oxidation resistance of carbon steels.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, diffusion coatings on gear materials via carburizing, nitriding, carbonitriding, boronizing, and chromizing to improve the wear resistance of carbon steels has been widely reported [7][8][9][10]. In addition to improvement on the hardness and wear resistance, boronizing and chromizing treatment can also improve the corrosion resistance and high-temperature oxidation resistance of carbon steels.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, only carbon (or nitrogen) substrates can be used, and component distortions may occur due to the process requiring higher temperature than the austenite start temperature of the steel. It has reported that applying TRD technique with plasma nitriding can improve the corrosion resistance [115].…”
Section: Comparison Of Surface Engineering Methodsmentioning
confidence: 99%
“…Previous studies show that carbon's affinity towards oxygen is always higher compared to nitrogen during the salt bath TRD process. So, plasma-nitriding sputtering and recondensation [22,23] processes were carried out with increased processing time to form a nitride phase with the vanadium carbide coating. The main objective of this cyclic process was to form larger primary carbides in a fine-tempered martensitic matrix and secondary carbides in a nanoscale during precipitation hardening [15].…”
Section: Phase and Microstructural Characterizationmentioning
confidence: 99%
“…Energy spectrum (Table 5) shows that zone 'Y' has enriched vanadium (66.61%), carbon (25.64%) and nitrogen (4.22%) due to dense VC-VN coating up to 6-8 µm. The thickness of VC and VC-VN coatings remains same, and the reason behind this could be mainly because of the replacement of carbon atoms by nitrogen atoms during the plasma-nitriding process [23].…”
Section: Phase and Microstructural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation